Evolution of Neurosurgery in Bangladesh (Bangladesh Journal of Neurosurgery, 2019)
The beginning of Neurosurgery is not very new in Bangladesh. Prof.Rashiduddin Ahmed established the first Neurosurgery unit in the then Institute of Postgraduate Medical Research (IPGMR) with only six beds in 1970. The first generation neurosurgeons left the field of neurosurgery in the safe hands of their disciples. There was a rapid progression of neurosurgery further both in private and in government level after 2000.In 1997 the first MS (Neurosurgery) course was started in IPGMR which was replaced by a 5-year residency course under Bangabandhu Sheikh Mujib Medical University (BSMMU) in 2010. Till now over 154 candidates are the active members of Bangaldesh Society of Neurosurgeons and are practicing independent neurosurgery. It is a very popular course and at present there are about 89 residents in various phases of the course in 4 institutions under BSMMU. With the available investigations, diagnostic facilities, operative facilities and good neuroanesthesia; now neurosurgeons also developed their skills in vascular neurosurgery, pediatric neurosurgery, endoscopic neurosurgery, spinal stabilization procedures, stereotactic neurosurgery and stem cell therapy. We are also hopeful that, very soon we would be able to achieve and develop our standard of neurosurgery to an international level by our determination and continuous effort, and by suitable and update learning, teaching and training.Bang. J Neurosurgery 2019; 8(2): 57-62